A Review of the Impact Factors Driving Vegetation Cover Change - Sun, Yutong; Zhang, Jing (International Journal of Agriculture and Food Sciences Research, 2024)
This review analyzes the driving factors behind vegetation cover change, focusing on the impacts of climate variability and human activities. Climatic factors such as temperature and precipitation change significantly influence vegetation dynamics, particularly in ecologically sensitive regions. Concurrently, human activities like urbanization, deforestation, and agricultural expansion exacerbate these impacts, leading to vegetation degradation. The integrated effects of climate change and anthropogenic actions are complex, requiring advanced methodologies for comprehensive understanding. This review underscores the need for multi-scale studies and sustainable management strategies to mitigate negative impacts on vegetation cover.